Processes, Participants Roles and Circumstances in Taylor Swift’s Song Bridge: Cruel Summer (A Discourse Analysis) - Chyntia Febiola; Sakinah Mawaddah; Dedek Aditia; Octa Dian; Linda Astuti Rangkuti (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
AbstractThis study is conducted based on a phenomenon of a viral song “Cruel Summer” by Taylor Swift. The “Cruel Summer”, particularly in the bridge part, is a well-known and is used as the part that fans have been waiting for. Many teenagers in Indonesia sing this song on TikTok. However in fact, the audience may not be aware of the intended message conveyed by the lyrics, only enjoy with the beat rhyme, without focus on how the experience and expression of emotions through this song. Thus, in this study, there is an interest to analyze the lyrics in terms of the experiential function of discourse analysis focusing on participant, process, and circumstances. The objective of this study is to find out if the lyrics success in conveying the emotions and experiences to the listeners. This study employed a qualitative research design. The data were the bridge lyrics of “Cruel Summer”. The data were analyzed by conducting data reduction, data display, and conclusion drawing. The results showed that the process, participants, and circumstances as part of the representation of experience as much as 80% of the bridge lyrics “Cruel Summer”. The dominant type is material process where this process is related to actions. The lyrics of the song reflect Taylor’s behaviours, including being intoxicated, crying, persisting, screaming, and so on. All the mentioned actions fall under the category of material process. Keywords: Cruel Summer, discourse analysis, experiential function